Reconceptualising Generative Grammar In English Language Teaching: From The Cognitive Turn To Classroom Implementation - budi Setiyo Utomo; Muhammad Miftahul Hia (Journal of Education, Linguistics, Literature and Language Teaching, 2026)
The generative tradition stands as a monumental pillar in twentieth-century formal linguistics, yet its direct translation into pedagogical frameworks remains heavily debated. This conceptual article explores the theoretical evolution of generative grammar and evaluates its implications for contemporary English Language Teaching (ELT) classrooms. Beginning with Noam Chomsky’s 1957 cognitive revolution, which shattered structuralist and behaviourist traditions, this paper traces the paradigm shifts through Government and Binding Theory up to the streamlined Minimalist Programme and recent developments in Strong Minimalist Thesis models (Chomsky, 2023). It examines the foundational dichotomies of competence versus performance and the structural dependent nature of human language governed by Universal Grammar (UG). By analyzing how these abstract constructs cross paths with Second Language Acquisition (SLA) models, the article provides a thorough synthesis of how generative principles can be systematically integrated into practical teaching methodologies. Specifically, the paper illuminates the empirical effectiveness of Form-Focused Instruction (FFI), Consciousness-Raising (CR) strategies, and Bill VanPatten’s Processing Instruction (PI), factoring in modern operational updates (VanPatten, 2021). Ultimately, the article argues that understanding a learner's interlanguage as a rule-governed, evolving grammar allows educators to move past superficial drilling methods. By prioritizing structured, targeted input over mere repetition, teachers can foster a deeper development of underlying linguistic competence rather than just automated performance. It concludes that while generative theory does not offer a simplistic classroom recipe, it provides essential diagnostic tools for modern language educators.